(untitled) (Sciences & Technology. A, exactes sciences, 2010)
The deposition by electrochemical way in the form of an iron thin film was studied on a vitreous carbon electrode in various aqueous and organic media. The deposit of iron was studied by cyclic voltammetry; the quantity of iron deposited was determined by integration of the cathodic and anodic peaks of Fe (0) and Fe (II) of the various media.